1989
DOI: 10.1111/j.1365-3083.1989.tb01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Immunoregulatory Effects of Monoclonal IgG‐Antibodies: Suppression and Enhancement of the Antibody Response

Abstract: Nine monoclonal IgG-anti-TNP antibodies were investigated for their ability to modulate anticarrier responses in mice immunized with sheep red blood cells-2,4,6-trinitrophenyl (SRBC-TNP) or keyhole limpet haemocyanin-TNP (KLH-TNP). The antibodies enhanced the anticarrier response when KLH-TNP was used as antigen but suppressed it when SRBC-TNP was used. The enhancing and suppressive effects were not exerted by entirely the same sets of antibodies. The suppression was correlated to efficient antigen binding, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…As stated above, orally immunized mice which received S. mutans saturated with MAb 6-11A demonstrated lower total levels of anti-S. mutans and anti-P1 serum IgG than animals which received bacteria alone or bacteria coated with a 0.1ϫ saturating concentration of MAb. Binding of different MAbs to a vaccine antigen prior to parenteral immunization has been reported to exert both suppressive and enhancing effects on the magnitude of the elicited response (5,69,80). In this instance, much of the decrease in anti-P1 serum IgG reactivity could be accounted for by a decrease in reactivity against the A region as measured by ELISA.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As stated above, orally immunized mice which received S. mutans saturated with MAb 6-11A demonstrated lower total levels of anti-S. mutans and anti-P1 serum IgG than animals which received bacteria alone or bacteria coated with a 0.1ϫ saturating concentration of MAb. Binding of different MAbs to a vaccine antigen prior to parenteral immunization has been reported to exert both suppressive and enhancing effects on the magnitude of the elicited response (5,69,80). In this instance, much of the decrease in anti-P1 serum IgG reactivity could be accounted for by a decrease in reactivity against the A region as measured by ELISA.…”
Section: Discussionmentioning
confidence: 81%
“…Binding of different monoclonal antibodies (MAbs) to a vaccine antigen prior to parenteral immunization has been reported to exert a variety of immunomodulatory effects, including suppression, enhancement, and differences in the specificity of the elicited response (4,5,6,69,80). Protection against colonization with any microorganism would be expected to depend on induction of antibodies of the correct specificity and isotype.…”
mentioning
confidence: 99%
“…We conclude that the IgE-mediated enhancement is mediated exclusively via CD23 and not via any other IgE receptor. To investigate whether our CD23-deficient mice were able to produce Abs in other situations, they were immunized with IgG/BSA-TNP complexes also known to enhance Ab responses in vivo (34,38). CD23-deficient mice were indeed capable of mounting an Ab response to IgG/BSA-TNP and even showed a higher response than wild-type controls (Fig.…”
Section: Impaired Ige-mediated Enhancement Of Ab Responses In Cd23-dementioning
confidence: 99%
“…They promote Fc receptor-mediated recognition by antigen-presenting cells (3,28). Immune complexes also activate the complement cascade (14,32). It has also been suggested that through binding to FcR and complement receptors, there is localization of the complex on follicular dendritic cells (DCs) which carry both types of receptor or that the complexes might directly stimulate B cells via their complement receptors (10).…”
mentioning
confidence: 99%